Advocacy of Ukraine in the period of martial law and restoration after the war: problems of legal regulation of the organization and activities - Tetyana VILCHYK (Revista Jurídica Portucalense, 2022)
By generally recognized standards, an independent bar is a necessary condition for the establishment of the rule of law and democracy in society, a necessary part of the justice system. The right to legal aid cannot be subject to any restrictions in time of war. The objective of the post-war reform is to bring the organization and activity of the Bar Association to the best international standards, strengthen the protection of human and citizen rights and freedoms, the institutional independence of the Bar. The article makes a brief analysis of the organization and activities of the Order of Lawyers of Ukraine during the conduct of hostilities in the territory of Ukraine for six months, shows the real actions of the Order of Lawyers at that time, analyzes the main changes in legislation, on how on the basis of which conclusions are drawn on the observance of lawyers' rights and the right to professional legal assistance during the introduction of martial law in Ukraine. The author formulated specific proposals aimed at further improving the organization and activities of the Bar Association, both in the modern and post-war period, in accordance with the requirements of Ukraine's European integration. Ucrânia.